Royalty Fee Penggunaan Merek pada Sistem Franchise UMKM Kebab Goceng di Kota Medan Persfektif Fatwa DSN MUI No.114/dsn mui/ix/2017 - Vita Hafsari; Annisa Sativa (LPPM Universitas Ekasakti Padang, 2023)
A franchise is an agreement regarding how to distribute products and services to customers. The party providing the license called the Franchisor, permits another party, called the Franchise, to run a product and service distribution business using the Franchisor's name in a certain area for a certain period of time. This business must be operated in accordance with the procedures and methods determined by the Franchisor. The Franchisor also provides support to the Franchisee, and in return, the Franchisee pays initial fees and royalties. In order to create a franchise business model that is in line with Islamic principles, it is necessary to apply the sharia value system as an ethical basis for business, aimed at preventing ethical violations in business (moral hazard). This research aims to examine the process of determining royalty fees for brand use within the framework of a franchise system, with a focus on the perspective explained in the DSN MUI Fatwa No:114/DSN-MUI/IX/2017. A review of the MUI's (Indonesian Ulema Council) fatwa and views on intellectual property rights and franchise practices shows the importance of complying with sharia principles in franchise agreements. These principles include clear profit calculations, profit sharing based on proportional ratios, and commitment to risks and losses. This case study focuses on the Kebab Goceng Franchise in Medan City, using a qualitative approach, including in-depth interviews and document analysis as data collection methods. The research results show that the Kebab Goceng franchise in Medan City has not implemented the DSN MUI Fatwa No: 114/DSN-MUI/IX/2017 in determining royalties. This determination is based on the criteria of fairness, mutual agreement and business sustainability. However, there are challenges regarding the interpretation and practical application of this fatwa.